2008
DOI: 10.1175/2007waf2005120.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Differences in Storm Rainfall from Hurricanes Isidore and Lili. Part II: Water Budget

Abstract: Part I of this two-part paper examined the satellite-derived rainfall accumulation and rain potential history of Hurricanes Isidore and Lili (2002). This paper (Part II) uses analyses from the Navy Operational Global Atmospheric Prediction System (NOGAPS) to examine the water budget and environmental parameters and their relationship to the precipitation for these two storms. Factors other than storm size are found to account for large volumetric differences in storm total rainfall between Lili and Isidore. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
5
11
0
Order By: Relevance
“…A comparison of precipitable water values when both TCs were located near this area (Figure 6c,d) shows that values for Irene exceeded 50 mm (Figure 6d) while those for Floyd approximated 40 mm. This finding supports previous research showing that higher amounts of moisture in the environment surrounding a TC can lead to a larger storm with more wide-spread rainfall [30][31][32][33][34]66].…”
Section: Rainfall Distribution Of Modern Stormssupporting
confidence: 91%
“…A comparison of precipitable water values when both TCs were located near this area (Figure 6c,d) shows that values for Irene exceeded 50 mm (Figure 6d) while those for Floyd approximated 40 mm. This finding supports previous research showing that higher amounts of moisture in the environment surrounding a TC can lead to a larger storm with more wide-spread rainfall [30][31][32][33][34]66].…”
Section: Rainfall Distribution Of Modern Stormssupporting
confidence: 91%
“…The moisture parameters are interpolated into 3‐h temporal resolution to match TMPA data. A simple expression of the vertically integrated water vapor budget is as follows [ Braun , 2006; Jiang et al , 2008b]: where TPW is the total precipitable water (mm, equivalent to kg m −2 ), HMC is the horizontal convergence of water vapor vertically integrated for the whole atmospheric column (mm hr −1 ), OSF is the ocean surface moisture flux (mm hr −1 ), P is precipitation rate (mm hr −1 ), and C is liquid and solid water stored as cloud (cloud storage, mm hr −1 ). Local changes of TPW and cloud storage terms are insignificant.…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
“… Rodgers and Pierce [1995] demonstrated that the SSM/I and ECMWF derived total precipitable water (TPW) fields influenced the precipitation distribution of Typhoon Bobbie (1992). Jiang et al [2008a, 2008b] compared the rainfall history and detailed water vapor budget of Hurricanes Isidore and Lili (2002) and found that large horizontal moisture convergence (HMC) and TPW were crucial to initiate and maintain the heavy rainfall before and during Isidore's landfall. However, no statistics‐based observational studies have documented, at least to the authors' current knowledge, on the relationship between TC rainfall and environmental moisture.…”
Section: Introductionmentioning
confidence: 99%
“…However, local water vapor is relatively limited (Jiang et al 2008;Simmonds et al 1999), and thus heavy rainfall is commonly associated with large-scale circulation in favor of moisture transport. Back to the middle of the twentieth century, scholars have laid the foundation for research on the relation between heavy rainfall and circulation in NC.…”
Section: Introductionmentioning
confidence: 99%